2016
DOI: 10.1160/th15-09-0704
|View full text |Cite
|
Sign up to set email alerts
|

Integration of flow studies for robust selection of mechanoresponsive genes

Abstract: Blood flow is an essential contributor to plaque growth, composition and initiation. It is sensed by endothelial cells, which react to blood flow by expressing > 1000 genes. The sheer number of genes implies that one needs genomic techniques to unravel their response in disease. Individual genomic studies have been performed but lack sufficient power to identify subtle changes in gene expression. In this study, we investigated whether a systematic meta-analysis of available microarray studies can improve their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…We also compared our microarray data to the list of >1600 shear-responsive genes obtained by meta-analysis of published microarray studies performed in vitro on human umbilical vein endothelial cells (Table V in the online-only Data Supplement). 39 We found that <50% of genes shown to be mechanically regulated in both data sets exhibit the same relationship with WSS. This observation further emphasizes the sensitivity of EC to physiological and mechanical stimuli that vary between in vitro and in vivo systems.…”
Section: Discussionmentioning
confidence: 68%
“…We also compared our microarray data to the list of >1600 shear-responsive genes obtained by meta-analysis of published microarray studies performed in vitro on human umbilical vein endothelial cells (Table V in the online-only Data Supplement). 39 We found that <50% of genes shown to be mechanically regulated in both data sets exhibit the same relationship with WSS. This observation further emphasizes the sensitivity of EC to physiological and mechanical stimuli that vary between in vitro and in vivo systems.…”
Section: Discussionmentioning
confidence: 68%
“…We have designed a protocol eliminating the need for a matrix and TGF-β) can be activated through mechanotransduction (Abuammah et al, 2018). The reaction of cells to mechanical forces, however, is complex, consisting of over 1,600 genes and 10,000 interactions with large amounts of crosstalk between signaling pathways (Frueh et al, 2013;Maimari, Pedrigi, Russo, Broda, & Krams, 2016). The identification of exact mechanisms activated within the bioreactor niche allowing ESCs to be expanded in the absence of feeder cells requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…as Aurora, Intraflagellar transporters and the homodimeric Platelet derived growth factor receptor (PdgfRαα) [37]. In the cardiovascular system endothelial and endocardial cells present monocilia [38 39], particularly in areas of low shear stress [40,41].…”
Section: Ciliary Mechanosensingmentioning
confidence: 99%
“…smooth muscle and endothelial cells. ECE and Et-B are both shear stress responsive [37,68] and expression is down-regulated upon applying shear forces [69].…”
Section: Endothelin Signalingmentioning
confidence: 99%
See 1 more Smart Citation